Accountability for Environmental Standards after Brexit. (June 2017) - Lee, Maria
This Opinion emphasises the importance of paying attention to how government will be held to account for implementing environmental standards once the UK has left the EU. It focuses on three, relatively simple, accountability mechanisms that have been taken for granted during our membership of the EU: the big sticks of Commission-plus-Court of Justice enforcement mechanisms and fines, a more subtle architecture of transparency and political accountability, and a series of EU legal principles that render judicial review before domestic courts more effective.